Refleksi pembelajaran daring di perguruan tinggi: Survey atas mahasiswa di sembilan perguruan tinggi Indonesia - Miftakhuddin Miftakhuddin; Orinton Purba; Saprudin Saprudin (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
This research discusses the quality of the higher education implementation of online learning in the last two years. The data were obtained from students who filled out open-ended electronic questionnaires. The data were then analyzed descriptively and qualitatively using Critical Success Factors (CSFs). However, this research highlights what other scholars have never found. First, the most prominent obstacles are lecturers' low digital literacy and the high level of distractors in the students’ physical environment. Second, students have distinctive commitments and preferences while participating in online learning. This research expounds that instead of gaining meaningful learning experiences, students prioritize filling out attendance lists and assignments submission. This research concludes that students’ commitments and preferences are not only linked to the experienced issues but also influenced by the lecturers' competence. Those who force themselves to study in ineffective learning are highly at risk of learning loss.